2020
DOI: 10.21470/1678-9741-2019-0159
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Efficacy of Amphotericin B in Candida Albicans Endocarditis Therapy: Systematic Review

Abstract: Introduction Although it is the most common agent among the fungal causes of endocarditis, Candida albicans endocarditis is rare. Objective To evaluate the efficacy of amphotericin B in the treatment of C. albicans endocarditis beyond a systematic review. Data search Articles in English, Spanish and Portuguese, conducted in the following databases: MEDLINE, LILACS, IBECS and SciELO, in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…It is imperative to distinguish the difference between commensal and invasive virulent growth; invasion is distinct from superficial colonization as the former is accompanied by inflammatory signals, resulting from the activated immune response. Clinical cases presenting C. albicans infections of the urogenital tract [1][2][3][4][5][6][7][8], kidney [1,7,[9][10][11][12][13], liver [14,15], lungs [16][17][18], spleen [19,20] and even the heart [21][22][23][24][25][26] have been reported. In rare cases, mostly in neonates, C. albicans can traverse the blood-brain barrier, resulting in infections of the brain [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative to distinguish the difference between commensal and invasive virulent growth; invasion is distinct from superficial colonization as the former is accompanied by inflammatory signals, resulting from the activated immune response. Clinical cases presenting C. albicans infections of the urogenital tract [1][2][3][4][5][6][7][8], kidney [1,7,[9][10][11][12][13], liver [14,15], lungs [16][17][18], spleen [19,20] and even the heart [21][22][23][24][25][26] have been reported. In rare cases, mostly in neonates, C. albicans can traverse the blood-brain barrier, resulting in infections of the brain [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Except for flucytosine, which acts on DNA synthesis, classic therapies mainly target the cell wall and membrane metabolism (Zida et al, 2017). The main therapeutic compounds are represented by polyenes: amphotericin B (Bezerra et al, 2020) or nystatin (Khalandi et al, 2020); azoles, such as imidazoles (Grimling et al, 2020); triazoles, such as fluconazole (Khalandi et al, 2020); allylamines with terbinafine (Kastamonuluoglu et al, 2020); morpholines, such as amorolfine (Ghannoum et al, 2019); and thiocarbamates with tolnaftate (Emam et al, 2019). Additionally, the β-glucan synthetase pathway is targeted by numerous compounds, such as echinocandin (Zida et al, 2017).…”
mentioning
confidence: 99%
“…Surgical interventions and prosthetic materials used in congenital and acquired heart diseases increase the risk of IE [1][2][3][4][5]7,19]. Although it has been reported that the risk of IE increases, especially in patients with prosthetic valves, more than 25% of patients have a history of valve surgery in natural valve IE [6].…”
Section: Discussionmentioning
confidence: 99%
“…Children with cancer may have multiple risk factors, such as tumor-related immunosuppression, nutritional deficiency, chemotherapy, and the presence of central catheters. The frequency of IE has increased significantly in patients in this group in recent years [2][3][4][5][6][7][8]19]. Twenty-three percent of our IE cases did not have structural heart disease and all of these patients had a history of central catheterization and received chemotherapy due to cancer.…”
Section: Discussionmentioning
confidence: 99%